Tall Cell Carcinoma with Reversed Polarity of the breast: Clinicopathological insights, molecular profile, and future therapeutic directions - Ye Lu; Xiangyi Kong; Wenxiang Zhang; Xiangyu Wang; Shengbin Pei; Yi Fang; Jidong Gao; Jing Wang (Breast, 2025)
Tall Cell Carcinoma with Reversed Polarity (TCCRP) is a rare and distinct subtype of invasive breast carcinoma, first described in 2003. It is histologically characterized by tall columnar epithelial cells with reversed nuclear polarity and shares morphological features with papillary thyroid carcinoma (PTC). However, its unique molecular signature, including IDH2 and PIK3CA mutations, differentiates it from other breast cancer subtypes. A retrospective systematic study of 91 published cases of TCCRP was conducted, including two cases from our institution. Clinical, pathological, molecular, and treatment-related data were collected and analyzed. Descriptive statistics and Kaplan-Meier survival analysis were employed to evaluate disease-free survival (DFS) and overall survival (OS). Subgroup analyses explored associations between clinical features, molecular markers, and outcomes. The median age at diagnosis was 64 years, with a predominance of small tumors (mean size: 10.4 mm, T1 stage). Histologically, hallmark features included reversed nuclear polarity (100 %), nuclear grooves, and intranuclear pseudoinclusions. Immunohistochemical analysis confirmed a triple-negative profile (ER-/PR-/HER2-) in most cases, with consistent breast-specific marker expression (GATA3, CK7). Molecular testing revealed frequent IDH2 R172 (84.6 %) and PIK3CA (72.5 %) mutations. Surgical management, predominantly breast-conserving surgery (BCS), was the primary treatment, with adjuvant therapies rarely utilized. At a median follow-up of 35.8 months, recurrence occurred in only 2.2 % of cases, and the overall survival rate was 100 %. TCCRP is a rare, low-grade breast cancer subtype with a favorable prognosis and low recurrence risk based on currently available data, but longer follow-up studies are needed to confirm this observation. Its distinct histological and molecular features enable accurate diagnosis and differentiation from other breast cancers and metastatic thyroid carcinoma. Given its indolent nature, conservative treatment strategies, including BCS, are effective, and adjuvant therapies can be minimized. Future research should explore targeted therapies for IDH2 and PIK3CA mutations to expand treatment options for this unique subtype.